Fundamental Solutions of the I-ST Plane Problem of Micropolar Elasticity with a Harmonically Varying Distortion Field - Dyszlewicz, J. (Engineering Transactions, 1992)
The paper deals with the I-st plane problem of micropolar elasticity in the case of a distortion field varying harmonically in time. Differential equations of the problem, expressed in terms of displacements and rotations, are solved by direct integration with the help of the Fourier integral transforms. Fundamental solutions are obtained for the displacements and rotations induced by concentrated distortions acting in an infinite plane. All limit cases of the fundamental solutions are given which arc relevant to derived theories